Protective effects of melatonin on testis histology following acute torsion-detorsion in rats - Mehri Mirhoseini; Fereshteh Talebpour Amiri; Abbas Ali Karimpour Malekshah; Zahra Rezanejad Gatabi; Elmira Ghaffari (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Testicular damage due to spermatic cord torsion may lead toinfertility. It is probably because of changes in oxidative stress factors such asmalondialdehyde. Objective: To investigate the protective effect of melatonin (MLT), as anantioxidant, on testicular damage induced by acute unilateral spermatic cord torsionand detorsion (T/D) in rats. Materials and Methods: In this experimental study, 48 adult male Wistar rats wererandomly divided into three groups (8 rats/group): sham group underwent rightscrotal surgery only., the T/D group underwent right testicular torsion (for 1 hr) anddetorsion, and the melatonin group underwent right testicular torsion, received 25μg/kg melatonin intraperitoneally immediately after surgery of T/D. Then thehistological parameters and malondialdehyde (MDA) changes were evaluated. Results: Torsion and detorsion decreased the diameter of the tubules significantlycompared to controls (p=0.003). Melatonin could increase the diameter, but it wasnot significant (p=0.26). The heights of the epithelium were constant in sham, T/D,and melatonin groups without any significant difference between groups (p=0.98).Based on Johnsen's score, spermatogenesis was normal in the sham group. Thetorsion significantly injured all lineage cells (p<0.001). There was no any spermatidor sperm in the seminiferous tubules. Melatonin improved the spermatogenesissignificantly (p=0.02), but could not improve MDA level significantly (p=0.99). Conclusion: Severe degenerative changes of testis were induced by acute unilateralspermatic cord torsion and detorsion in rats, but it had no effect on MDA level.